A systematic investigation of the tribological behaviour of oxides formed on AlSiTiN, CrAlTiN, and CrAlSiTiN coatings - Lim, Hooi Peng; Jiang, Zhong-Tao; Gan, Melvin Jet Hong; Nafarizal Nayan; Chee, Fuei Pien; Soon, Chin Fhong; Naveed Hassan; Liew, Willey Yun Hsien (Elsevier, 2022)
Changes with temperature in the microstructure and oxide formation of AlSiTiN, CrAlTiN, and CrAlSiTiN coatings were systematically studied using various characterisation techniques. By correlating these results with their tribological behaviour seen in the reciprocating sliding tests, it was concluded that SiO2 was more lubricous than Cr2O3, and provided better wear protection. Although an increase in the amount of SiO2 produced in the tribo-layer resulted in a greater lubricating effect, Cr2O3 produced a much lesser of such benefit. The effect of SiO2 as lubricant was also seen in machining. In the machining of stainless steel at 100 m/min, where flank and notch wear was due to abrasion and mechanical cracking, the CrAlSiTiN coated tools with the highest hardness, H/E, and H3/E2 exhibited the highest wear resistance. However, AlSiTiN coated tools demonstrated reduced flank wear and the lowest wear in machining at 200 m/min. The formation of SiO2 could account for this low level of wear.